Origin, Expansion, and Divergence of ETHYLENE-INSENSITIVE 3 (EIN3)/EIN3-LIKE Transcription Factors During Streptophytes Evolution - Mao, Kexin; Zhang, Minghui; Kong, Yadong; Dai, Shanshan; Wang, Yong; Meng, Qingwei; Ma, Nana; Lv, Wei (Frontiers in Plant Science, 2022)
The transition of plants to land required several regulatory adaptive mechanisms. Little is known about these mechanisms, but they no doubt involved the evolution of transcription factor (TF) families. ETHYLENE-INSENSITIVE 3 (EIN3)/EIN3-LIKE (EIL) transcription factors (TFs) are core components of the ethylene signaling pathway that play important roles in almost every aspect of plant development and environmental responses by regulating the transcription of numerous genes. However, the evolutionary history of EIN3/EIL TFs, which are present in a wide range of streptophytes, is still not clear. Here, to explore the evolution and functions of EIN3/EIL TFs, we performed phylogenetic analysis of these TFs and investigated their gene and protein structures as well as sequence features. Our results suggest that the EIN3/EIL TF family was already was already present in the ancestor of streptophyte algae. Phylogenetic analysis divided the EIN3/EIL TFs into three groups (Group A–C). Analysis of gene and protein structure revealed that most of the structural features of these TFs had already formed in ancient lineages. Further investigation suggested that all groups have undergone several duplication events related to whole-genome duplications in plants, generating multiple, functionally diverse gene copies. Therefore, as plants colonized terrestrial habitats and evolved key traits, the EIN3/EIL TF family expanded broadly via multiple duplication events, which could have promoted their fundamental neo- and sub-functionalization to help plants adapt to terrestrial life. Our findings shed light on the functional evolution of the EIN3/EIL TF family in the streptophytes.